The Nixon revolution and the third world - W. M. Scammell (Intereconomics, 1972)
In the dramatic events and the whirl of talk which has followed the Nixon economic measures, the developed countries have been preoccupied with the new situation created for them. The ultimate impact of this fundamental policy-change upon the poor two-thirds of the world has been virtually ignored.
Keywords: 330; Developing countries